Health Financing in the Republic of Gabon : Policy Note - Saleh, Karima; Couttolenc, Bernard F.; Barroy, Helene (World Bank, Washington, DC, 2016)
This is a policy note following from the book Health Financing in the Republic of Gabon. The book is a comprehensive assessment of health financing in the Republic of Gabon. The book reviews the health financing situation in light of the government’s introduction of a national health insurance program and its commitment to achieving universal health insurance coverage in the medium term. The book provides a diagnostic of the situation in light of recent data from the demographic and health survey, updated national health accounts, and a review of public expenditures in the health sector. Additionally, it performs a benchmarking exercise to assess how Gabon performs in its health spending and health outcomes compared to countries of similar income and compared to countries in the region. A forthcoming household survey is expected to provide better information on financial protection against illness costs. This book attempts to diagnose Gabon’s current situation in regards to achieving universal health coverage. Gabon should be commended for its commitment to improving health indicators of the poor and the underserved. The book shows that while the government has set an ambitious goal for itself, several challenges exist in meeting these objectives in the medium term as follows (i) resource mobilization efforts are a priority to sustain its programs financially; (ii) to prioritize resources for areas considered, value for money, to improve equity in access and delivery of health services, with particular focus on primary care, public health program, and quality of care; (iii) to increase the population’s coverage under the national health insurance program, with focus on the poor and the informal sector workers; and (v) to consider areas that would improve efficiency and reduce costs. The book is timely, given that the government has recently produced, the Plan Social. It provides a diagnostic of the health sector and provides key recommendations and options for the government to consider in the short to medium term.